Competition, taxation and economic growth - Yilmaz, Ensar (ELSEVIER, 2013)
The paper mainly examines the relationship between economic growth, tax policy and sectoral labor distribution in an endogenous growth model with expanding varieties. For analyzing these relationships, we consider an economy where three sectors of production are vertically integrated: final goods sector, intermediate goods sector and research sector. We show that the extent of imperfect competition in the intermediate products market affects both economic growth and the allocation of the available labor to all the sectors employing this input. The resources from capital taxation, which are used for financing research sector, have a U-shaped effect on growth and lead to a movement of the labor from research sector to final goods sector. Additionally, we show that if there exists a higher competitive structure in an economy, the probability of the positive effect of an increase in tax on growth gets higher. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Endogenous growth; Capital tax; Competition; INNOVATION; MODEL; Business & Economics